Social Distancing Detection with Deep Learning Model - Hou Y.C.; Baharuddin M.Z.; Yussof S.; Dzulkifly S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Inspection equipment; Learning systems; Object detection; Object recognition; Coronaviruses; Detection tools; Learning models; Model-based OPC; Multiple people; Pedestrian detection; Real-time application; Safe distance; Deep learning